2015
DOI: 10.1371/journal.pone.0140492
|View full text |Cite
|
Sign up to set email alerts
|

Deregulated Expression of SRC, LYN and CKB Kinases by DNA Methylation and Its Potential Role in Gastric Cancer Invasiveness and Metastasis

Abstract: Kinases are downstream modulators and effectors of several cellular signaling cascades and play key roles in the development of neoplastic disease. In this study, we aimed to evaluate SRC, LYN and CKB protein and mRNA expression, as well as their promoter methylation, in gastric cancer. We found elevated expression of SRC and LYN kinase mRNA and protein but decreased levels of CKB kinase, alterations that may have a role in the invasiveness and metastasis of gastric tumors. Expression of the three studied kina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 70 publications
1
28
0
1
Order By: Relevance
“…In addition to frequent straggly phosphorylation, abnormal expressions of Src protein were also seen in neoplastic diseases. Elevated expression of Src protein was found to be related to invasiveness and metastasis in gastric tumors . Studies also asserted that overexpression of Src was observed in high‐grade leiomyosarcoma, making Src a potential valuable diagnostic marker for this soft tissue sarcoma .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to frequent straggly phosphorylation, abnormal expressions of Src protein were also seen in neoplastic diseases. Elevated expression of Src protein was found to be related to invasiveness and metastasis in gastric tumors . Studies also asserted that overexpression of Src was observed in high‐grade leiomyosarcoma, making Src a potential valuable diagnostic marker for this soft tissue sarcoma .…”
Section: Discussionmentioning
confidence: 99%
“…Hras was up-regulated in rats with gastric precancerous lesions (Shen et al 2008). Myc as a possible biomarker for GC, the mRNA expression, protein expression, as well as gene copy numbers were evaluated in human GC samples (De Souza et al 2013;Mello et al 2015). SRC, a cell cycle regulator and transcriptional factor, was up-regulated in human GC samples (Mello et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Myc as a possible biomarker for GC, the mRNA expression, protein expression, as well as gene copy numbers were evaluated in human GC samples (De Souza et al 2013;Mello et al 2015). SRC, a cell cycle regulator and transcriptional factor, was up-regulated in human GC samples (Mello et al 2015). Gnai3 was significantly associated with gastric cardia cancer risk (Li et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Yamada Y et al revealed that overexpression of PLOD1 was closely related to poor survival and downregulation of PLOD1 can decrease the progression of BC [40]. CKB was participated in metabolic processes involving glycolysis and could serve as a biomarker for predicting tumor progression [41]. However, the precise role of CKB in the occurrence and progression of BC has not been well studied.…”
Section: Discussionmentioning
confidence: 99%